To Live or to Die: Prosurvival Activity of PPARγ in Cancers - Y. Lynn Wang; Qi Miao (PPAR Research)
The role of PPARγ in tumorigenesis is controversial. In this article, we review and analyze literature from the past decade that highlights the potential proneoplastic activity of PPARγ. We discuss the following five aspects of the nuclear hormone receptor and its agonists: (1) relative expression of PPARγ in human tumor versus normal tissues; (2) receptor-dependent proneoplastic effects; (3) impact of PPARγ and its agonists on tumors in animal models; (4) clinical trials of thiazolidinediones (TZDs) in human malignancies; (5) TZDs as chemopreventive agents in epidemiology studies. The focus is placed on the most relevant in vivo animal models and human data. In vitro cell line studies are included only when the effects are shown to be dependent on the PPARγ receptor.